Metagenome microbial communities of bottom sediments of the Kara Sea ... - LIN SB RAS (MGnify, 2020)
Metagenomic analysis of the microbial community in the bottom sediments Kara Sea shelf Yenisei Gulf and Gyda Bay by pyrosequencing ...